The behavioural intention to use Facebook among Malaysian public universities as technology alternative tool for e-learning: the mediating role of end user satisfaction - Nur Fathiah, Mohd Bashri (2016)
Nowadays, Facebook is one of the most popular Social Networking Sites (SNS) among the tertiary education students. This site is seen to be used as technology alternative to support the main Learning Management System (LMS) that is provided by the university. However, the real situation nowadays, the students prefer to use Facebook compares to LMS as their e-Learning tool for communicating and sharing knowledge among them. Two well-known models are integrated in this study which is Unified Theory of Acceptance and Use of Technology (UTAUT) and End User Computing Satisfaction (EUCS) for better understanding the vital factors that stimulate students' Behavioural Intention (BI) in using Facebook as e-Learning tool. The sample size comprised of 472 students in Malaysia's Public Universities taken through the quota sampling technique. Thus, the total of 411 usable questionnaires was used for further analysis. Based on data analysis by utilizing PLS SEM method, the results supported the hypothesized of direct effects relationship between all four core factors of UTAUT (Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Conditions) and EUCS on BI. Meanwhile, EUCS mediated the relationship between all four core factors of UTAUT on BI. These findings also supported the view that the integration between satisfaction and acceptance models increases the exploratory power on the users' behaviour of interest in using information technology. Lastly, theoretical, methodological and practical implications are discussed.